Assisted reproductive technology and interactions between serum basal FSH/LH and ovarian sensitivity index - He, Yumei; Liu, Ling; Yao, Fei; Sun, Chenyu; Meng, Muzi; Lan, Yunzhu; Yin, Chengliang; Sun, Xingyu (Frontiers in Endocrinology, 2023)
This study aimed to investigate whether the FSH (follicle-stimulating hormone) / LH (Luteinizing hormone) ratio correlates with ovarian response in a cross-sectional retrospective study of a population with normal levels of anti-Müllerian hormone (AMH).We conclude that increased basal FSH/LH in the AMH normal group reduces the ovarian response to exogenous Gn. Meanwhile, basal FSH/LH of 3.5 was found to be a useful diagnostic threshold for assessing ovarian response in people with normal AMH levels. Ovarian sensitivity index (OSI) can be used as an indicator of ovarian response in assisted reproductive technology (ART) treatment.